Effects of design parameters on the centering performance of nose landing gear for a certain aircraft - Shuai Zhao; Ye Zhao (Advances in Mechanical Engineering, 2024)
The centering mechanism of the nose landing gear is crucial for aircraft operational safety, particularly during the takeoff and landing processes. To address the failure of the return function observed in a certain aircraft, this paper establishes a dynamic model that can effectively characterize the return motion characteristics of the landing gear, considering the synergistic effect of the landing gear buffer device, the shimmy damper, and the centering mechanism comprehensively. On this basis, the four key parameters are studied in depth, including the initial filling pressure of the buffer device, the friction moment of the shimmy damper, the damping coefficient of the shimmy damper, and the contact friction coefficient of the centering mechanism. The results reveal that the return driving moment acting on the piston rod of the nose landing gear increases slowly with the increase in steering angle. At the 90° steering angle, the peak value of the return driving moment is 43.97 Nm. Among the parameters studied, compared with the initial filling pressure and the friction moment of the shimmy damper, the contact friction coefficient of the cam has the most significant effect on the return function.